«Небо великих надій»: архітектурний екфразис у романі П. Загребельного Диво - Білик, Наталія (Slavia Orientalis, 2025)
At the present stage in the development of comparative studies, the multifaceted phenomenon of ekphrasis has not lost its relevance; features of architectural ekphrasis are observed in Pavlo Zahrebelny’s novel Miracle. The research is based on cultural semiotic and structural‑semantic analysis methods in combination with descriptive and comparative‑typological approaches. Resultingly it turns out that there are complexes of consolidated, attributed, discrete ekphrasis of the Temple and related urban types of architecture. Through all the time planes of the novel, a vertical of ekphrasis develops, symmetrical to the main image of the Temple, presented in the work by the Church of the Mother of God and St. Sophia Cathedral. In the aggregate outlines of the temples topography, revealed by the contents of the ekphrasis, it is necessary to distinguish the resonant repetition of the elemental expressiveness of domes, naves, and iconostasis inherent within the genre. The manifested refrain of artistic language within the art of architecture intensifies and symbolizes a unifying semantic harmony, the sound of which leitmotivizes the desire for a higher comprehension of the sources of joy, goodness, beauty and harmony. From this perspective, the “Miracle” draws a line of meaning, which depicts the overall configuration, focused on the appreciation of benevolence, philanthropy, and on the outlines of humanization among the features of ekphrastic discourse. And therefore the multidimensional poetics of ekphrasis with its complex of aggregated, attributed, discrete ekphrasis of temple and related urban architectural types becomes noticeable. Selected features of ekphrasis are systematized by the integral main image of the Christian Temple. In the combined outlines, the topography of the temple is revealed by the expressiveness of the poetics of the genre: domes, nave, iconostasis. In these artistic language manifestations of the art of architecture, the leitmotif is the desire to understand the sources of joy, goodness, beauty, harmony, to appreciate benevolence, philanthropy. In these outlines of humanization, the semantic conclusion of the ekphrasis is the special “skyline” of church domes, which lead to the horizons of sacred thought as to the creation of a temple in the human soul, and from this semantic palette shaded is a kind of “sky of great hopes”, commensurate with the postulate of the “affirmation of faith”, of the Christian humanistic civilizational choice in the sense of eternal value.